Legal Protection for Patients and Health Personnel from an Islamic Legal Perspective - Azzahra Chandra Syafira; Irwansyah Alfaqih; Baharuddin Siregar; Sri Rahayu (LPPM UIKA Bogor, 2024)
Health workers are a profession that plays a big role in the health sector. Without us realizing, there are many problems that health workers face when they have to deal with patients. This research reviews